Tafasitamab plus lenalidomide in relapsed or refractory diffuse large B-cell lymphoma (L-MIND): a multicentre, prospective, single-arm, phase 2 study. Issue 7 (July 2020) - Salles, Gilles; Duell, Johannes; González Barca, Eva; Tournilhac, Olivier; Jurczak, Wojciech; Liberati, Anna Marina; Nagy, Zsolt; Obr, Aleš; Gaidano, Gianluca; André, Marc; Kalakonda, Nagesh; Dreyling, Martin; et al.
Summary: Background: Patients with relapsed or refractory diffuse large B-cell lymphoma who are ineligible for autologous stem-cell transplantation have poor outcomes and few treatment options. Tafasitamab (MOR208) is an Fc-enhanced, humanised, anti-CD19 monoclonal antibody that has shown preclinical and single-agent activity in patients with relapsed or refractory B-cell malignancies. Preclinical data suggested that tafasitamab might act synergistically with lenalidomide. We aimed to assess the antitumour activity and safety of tafasitamab plus lenalidomide in patients with relapsed or refractory diffuse large B-cell lymphoma who were ineligible for autologous stem-cell transplantation. Methods: In this multicentre, open-label, single-arm, phase 2 study (L-MIND), patients older than 18 years with histologically confirmed diffuse large B-cell lymphoma, who relapsed or had refractory disease after previous treatment with one to three systemic regimens (with at least one anti-CD20 therapy), were not candidates for high-dose chemotherapy and subsequent autologous stem-cell transplantation, had an Eastern Cooperative Oncology Group performance status of 0–2, and had measurable disease at baseline were recruited from 35 academic and community hospitals in ten countries. Patients received coadministered intravenous tafasitamab (12 mg/kg) and oral lenalidomide (25 mg/day) for up to 12 cycles (28 days each), followed by tafasitamab monotherapy (in patients with stable disease or better) until disease progression. The primary endpoint was the proportion of patients with an objective response (centrally assessed), defined as a complete or partial response according to the 2007 International Working Group response criteria for malignant lymphoma. Antitumour activity analyses are based on all patients who received at least one dose of both tafasitamab and lenalidomide; safety analyses are based on all patients who received at least one dose of either study medication. Recruitment is complete, and the trial is in follow-up. This trial is registered with ClinicalTrials.gov, NCT02399085 . Findings: Between Jan 18, 2016, and Nov 15, 2017, 156 patients were screened: 81 were enrolled and received at least one dose of either study medication, and 80 received at least one dose of both tafasitamab and lenalidomide. Median follow-up was 13·2 months (IQR 7·3–20·4) as of data cutoff on Nov 30, 2018. 48 (60%; 95% CI 48–71) of 80 patients who received tafasitamab plus lenalidomide had an objective response: 34 (43%; 32–54) had a complete response and 14 (18%; 10–28) had a partial response. The most common treatment-emergent adverse events of grade 3 or worse were neutropenia (39 [48%] of 81 patients), thrombocytopenia (14 [17%]), and febrile neutropenia (ten [12%]). Serious adverse events occurred in 41 (51%) of 81 patients. The most frequently reported serious adverse events (in two or more patients) were pneumonia (five [6%]), febrile neutropenia (five [6%]), pulmonary embolism (three [4%]), bronchitis (two [2%]), atrial fibrillation (two [2%]), and congestive cardiac failure (two [2%]). Interpretation: Tafasitamab in combination with lenalidomide was well tolerated and resulted in a high proportion of patients with relapsed or refractory diffuse large B-cell lymphoma ineligible for autologous stem-cell transplantation having a complete response, and might represent a new therapeutic option in this setting. Funding: MorphoSys.